The Optimalization Legal Role of Contracts in the Settlement of Business Disputes Between the Parties of Contract Agreement - Retnowati, May Shinta; Amrullah, Muhammad Ilham; Rachmawati, Andini (FENOMENA, 2023)
There are many problems in Islamic civil transactions, including muamalah activities carried out in the midst of society when running a business. This time the role of agreement law (contract) in the settlement of business disputes between the parties in the contract agreement, in which the dispute will be vulnera-ble to occur in a business relationship, due to the absence of good faith, the desire to increase the profits that can be achieved, and the existence of default, which is not closing the possibility of a loss experi-enced by one of the parties in the business relationship who entered into the agreement or contract, there-fore the law of the agreement (contract) is very necessary in order to protect the parties in the business re-lationship so as not to experience losses that can occur at any time. . This research method uses library research that takes references from several literatures. The results of this study are that at the beginning of business activities there must be a law of agreement or often referred to as a contract to guard so that a business relationship can run well, according to what is desired and agreed upon by the parties who make an agreement or contract. Because basically a dispute is a situation that often appears in the busi-ness world, where the dispute must be resolved